Implementation of the Computer-Based National Assessment-Oriented School Literacy Movement Policy for Elementary School Students in Bireuen District - Ruwaeda, Ruwaeda; Siraj, Siraj; Iskandar, Iskandar (Indonesian Journal of Education and Mathematical Science, 2024)
The school literacy movement (SLM) is more than just reading and writing but includes thinking skills according to stages and literacy components. SLM aims to develop student ethics through the development of a literacy ecosystem, so that students become lifelong learners. But the problem is difficulty listening and telling stories longer, difficulty understanding the intent and purpose of SLM. This study aims to: (1) describe planning, (2) describe implementation, (3) describe the evaluation of the implementation of the school literacy movement (SLM) policy oriented to computer-based national assessment in elementary school students in Bireuen Regency. This research is a field study using a qualitative approach conducted at SD 4 in Bireuen Regency. The data was collected through interviews, and observation. Data analysis techniques are carried out through data reduction and data presentation. The results showed that: (1) Computer-based National Assessment-oriented School Literacy Movement policy implementation planning: (a) goal and target planning, (b) problem identification, (c) stakeholder identification, (d) resources and budget, (e) strategy, (f) monitoring and evaluation, (g) improvement and learning, (h) problem formulation, (i) recommendations, (j) result monitoring, (k) performance evaluation, (l) Computer-based National Assessment-oriented School Literacy Movement policy implementation. (2) Implementation of Computer-based National Assessment-oriented School Literacy Movement policy: (a) allocating natural resources and human resources, (b) hardware and software, (c) technological infrastructure, (d) educational content, (e) training and professional development, (f) coaching and supervision, (g) administration and reporting, (h) communication and awareness, (i) research evaluation and budget, (j) awards and recognition, (l) ensuring data security and privacy,  (k) Stakeholder involvement, (l) Achievement of targets in implementation, (m) Quality in implementation, (n) communication and coordination in implementation. (3) Evaluation of Computer-based National Assessment-oriented School Literacy Movement Implementation for Elementary School Students in Bireuen District, which are the effectiveness of policy implementation, efficient policy implementation, satisfactory policy implementation, equality and equity of implementation, student response to implementation and accuracy of policy implementation.